FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP REVALUASI ASET TETAP - Dwi Megowati (2017)
This study aims to prove the factors that affect the revaluation of fixed assets. The population in this study are all companies listed in Indonesia Stock Exchange (BEI) in 2014-2016. The technique of determining the sample using purposive sampling method. There are 358 companies qualified as sample. Data analysis method of this research is logistic regression analysis with significance level 5%. The results of this study show that Leverage, Liquidity and operating cash flow not affect on the revaluation of fixed assets., while fixed asset intensity has an effect on fixed asset revaluation.